2019
DOI: 10.1002/jbm.a.36680
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated hyaluronan‐containing artificial extracellular matrices promote proliferation of keratinocytes and melanotic phenotype of melanocytes from the outer root sheath of hair follicles

Abstract: The aim of this work was to establish improved cultivation conditions for human keratinocytes (HUKORS) and melanocytes (HUMORS) from the outer root sheath (ORS) of human hair follicles for purposes of generating an epidermal graft. To this end, the cells were cultivated on artificial extracellular matrix coatings composed of collagen (COLL) and hyaluronan (HA) with varying sulfation degrees. HUKORS and HUMORS were characterized based on their morphology and proliferation, marker gene expression, protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
3
4
0
Order By: Relevance
“…In previous research, sHA showed great biocompatibility and had been used as a main component to synthesize biomaterials. However, Dieter et al reported that sHA reduces the proliferation rate of primary rat calvarial osteoblasts by affecting their cell cycle . Similar results were found in our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In previous research, sHA showed great biocompatibility and had been used as a main component to synthesize biomaterials. However, Dieter et al reported that sHA reduces the proliferation rate of primary rat calvarial osteoblasts by affecting their cell cycle . Similar results were found in our study.…”
Section: Discussionsupporting
confidence: 89%
“…After sHA is immobilized on the collagen surface, its interaction with free cytokines in the medium will be reduced. , Therefore, the proliferation of corneal epithelial cells on collagen membranes with sHA coatings is unaffected. Studies on biomaterials using sHA as main raw materials have shown that immobilized sHA had no adverse effect on cell proliferation. ,, The results of our animal experiments also confirmed that the re-epithelialization of the wounded cornea was unaffected by the sHA coating, demonstrating that the application of sHA by the coating method is biocompatible.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…carcinoma cell lines [37,38]. We assumed that the weak adherence of both cell types could be reinforced by activating the PS surface chemistry, which could subsequently corroborate cell proliferation.…”
Section: Polymer Layer Formation By Laccase and Laccase-substrate Tre...mentioning
confidence: 99%
“…To the best of our knowledge, this study is the first assessment of the laccase-based surface modification effects on those two cell lines [ 33 , 34 , 35 , 36 ]. NHEMs are well known for easily detaching in the process of differential trypsinization, and the adherence of NTERA-2 cells is low as in most embryonic carcinoma cell lines [ 37 , 38 ]. We assumed that the weak adherence of both cell types could be reinforced by activating the PS surface chemistry, which could subsequently corroborate cell proliferation.…”
Section: Introductionmentioning
confidence: 99%